Proteomic Characterization, Biodistribution, and Functional Studies of Immune-Therapeutic Exosomes: Implications for Inflammatory Lung Diseases - Elashiry, Mahmoud; Elsayed, Ranya; Elashiry, Mohamed M.; Rashid, Mohammad H.; Ara, Roxan; Arbab, Ali S.; Elawady, Ahmed R.; Hamrick, Mark; Liu, Yutao; Zhi, Wenbo; Lucas, Rudolf; Vazquez, Jose; et al. (Frontiers in Immunology, 2021)
Dendritic cell (DC)-derived exosomes (DC EXO), natural nanoparticles of endosomal origin, are under intense scrutiny in clinical trials for various inflammatory diseases. DC EXO are eobiotic, meaning they are well-tolerated by the host; moreover, they can be custom-tailored for immune-regulatory or -stimulatory functions, thus presenting attractive opportunities for immune therapy. Previously we documented the efficacy of immunoregulatory DCs EXO (regDCs EXO) as immunotherapy for inflammatory bone disease, in an in-vivo model. We showed a key role for encapsulated TGFB1 in promoting a bone sparing immune response. However, the on- and off-target effects of these therapeutic regDC EXO and how target signaling in acceptor cells is activated is unclear. In the present report, therapeutic regDC EXO were analyzed by high throughput proteomics, with non-therapeutic EXO from immature DCs and mature DCs as controls, to identify shared and distinct proteins and potential off-target proteins, as corroborated 2 by immunoblot. The predominant expression in regDC EXO of immunoregulatory proteins as well as proteins involved in trafficking from the circulation to peripheral tissues, cell surface binding, and transmigration, prompted us to investigate how these DC EXO are biodistributed to major organs after intravenous injection. Live animal imaging showed preferential accumulation of regDCs EXO in the lungs, followed by spleen and liver tissue. In addition, TGFB1 in regDCs EXO sustained downstream signaling in acceptor DCs. Blocking experiments suggested that sustaining TGFB1 signaling require initial interaction of regDCs EXO with TGFB1R followed by internalization of regDCs EXO with TGFB1-TGFB1R complex. Finally, these regDCs EXO that contain immunoregulatory cargo and showed biodistribution to lungs could downregulate the main severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) target receptor, ACE2 on recipient lung parenchymal cells via TGFB1 in-vitro. In conclusion, these results in mice may have important immunotherapeutic implications for lung inflammatory disorders.